Relacja mistrz – uczeń w Drugim Liście do Tymoteusza.Analiza socjoretoryczna - Pakowski, Grzegorz (Warszawskie Studia Teologiczne, 2019)
Saint Paul's epistles, especially so called pastoral epistles, bring us an unique picture of person being simultaneously master and disciple. Paul is aware that as an apostle he is always servant of God. At the same time, as a teacher he already has own disciples, like saint Timothy. The article comes up with an analysis of the relationship between master and disciple in 2Tm. Using so called socio-rhetorical approach, it compares Paul's model to the upbringing models known in the ancient Mediterranean: Jewish, Greek and Roman conceptions. After analysing inner texture, intertexture and social and cultural texture as well as the sacred texture it turns out that Paul made his own model of such relationship. While using many patterns form previously know models, he states that the relationship between the master and the disciple is in fact the relationship between three persons: the master, the disciple and God. Both master and disciple need to receive grace from God. Master may give his disciple an example of own life in order to inspire him. He is also able to show his disciple paths leading to God. However, God is the one who chooses his disciples, who enables them to gain both knowledge and virtues, and finally who is the first and the most important master.